2017
DOI: 10.1038/s41598-017-07859-5
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Toll-like receptors in eutopic and ectopic endometrium and its implication in the inflammatory pathogenesis of adenomyosis

Abstract: In this study, we investigated the expression profiles of Toll-like receptors(TLRs) in eutopic endometrium(EU) and ectopic endometrium(EC) and its implication in the inflammatory pathogenesis of adenomyosis. Thirty adenomyosis patients who underwent laparoscopy were recruited in this study. We tested the mRNA and protein expression of TLRs, and the mRNA expression of IL-6 and IL-8 in EU and EC of adenomyosis patients, and control endometrium without adenomyosis(CE). We found that the mRNA expression of IL-6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In addition, the correlation between the expression of HMGB1, TLR4, NF-κB and TNF-α in MEOC group was evaluated and it was demonstrated that all the parameters were positively correlated with each other. It is known that the HMGB1/TLR4 signaling pathway regulates cell proliferation and survival, and creates a tumor microenvironment that facilitates tumor growth by inducing immune cell expansion and integrating inflammatory responses (19). Considering these previous findings and those obtained from the present study, it was therefore concluded that increased HMGB1/TLR4 in the inflammatory immune signaling system may be involved in MEOC tumor stage and differentiation.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, the correlation between the expression of HMGB1, TLR4, NF-κB and TNF-α in MEOC group was evaluated and it was demonstrated that all the parameters were positively correlated with each other. It is known that the HMGB1/TLR4 signaling pathway regulates cell proliferation and survival, and creates a tumor microenvironment that facilitates tumor growth by inducing immune cell expansion and integrating inflammatory responses (19). Considering these previous findings and those obtained from the present study, it was therefore concluded that increased HMGB1/TLR4 in the inflammatory immune signaling system may be involved in MEOC tumor stage and differentiation.…”
Section: Discussionsupporting
confidence: 78%
“…vii) TLR4. The expression of TLRs (TLR1, 2, 4, 5 and 9) is higher in the ectopic endometrium and eutopic endometrium in adenomyosis as compared with the normal endometrium, and positively correlates with IL-6 and IL-8 (74). Similar to adenomyosis, TLR4 is overexpressed in endometriosis, indicating that both conditions are a state of inflammatory pathology (75).…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%
“…A noticeably reduced rate of spontaneous pregnancy was reported in women with concomitant adenomyosis who underwent surgical treatment of rectovaginal and bowel endometriosis compared with those without adenomyosis (11.9% vs. 43.0%) [ 3 ]. A number of scholars demonstrated that there were abnormal aggregation of inflammatory immune cells and cytokines in adenomyosis nodes, including dendritic cells, macrophages, neutrophils, tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), IL-8, nerve injury-induced protein1, and cyclooxygenase-2 (COX-2) [ 4 6 ]. In addition, disturbed uterine peristalsis, anatomical distortion of uterine cavity, altered uterine oxidative stress environment, and changing endometrial steroid metabolism may all contribute to the impaired endometrial receptivity in adenomyosis patients [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%